The Practice of Human Resource Management in Canada - Bob Barnetson; Jason Foster (AU Press, 2024)
This introductory human resource management (HRM) textbook provides students with an overview of the major domains of human resource management (the "how-to") with a focus on the practical application of the most recent HRM research and best practices. Students will learn to understand, anticipate, and respond to how power, profit, and intersectionality shape the practice of HRM. Moving beyond the typical procedure-oriented textbook, Barnetson and Foster provide thought-provoking political analysis to better prepare students for the real-world practice of human resource management.
Keywords: 330; human resources; human resources management; personnel management; labor; labour; employment; labour relations; labor relations; HRM; law; employment law; workflow; business strategy; job design; recruitment; hiring practices; business practices; textbook; introductory textbook; wages; benefits; employee; worker; staff; unions; collective bargaining; performance evaluation; performance management; discipline; termination; Canada; Canadian; workforce